(untitled) (International Association of Biologicals and Computational Digest, 2023)
Comparatively a newer discipline, ethnobotany examines the various rules that govern interactions between people and plant. People have been associated with plants since time immemorial and dependent for their various uses such as food, fodder, and medicine. Ethnobotany is the study of the utilitarian relationship between people and plant in their surroundings, as well as medicinal uses. This ethnobotanical study is providing the information of ethnobotany, concept, Historical background, traditional knowledge and threats of ethnobotany. This paper focuses on the ethnobotanical researches of India and Gujarat. In India, 500 networks with 227 different Ethnic groups were home to about 7500 different kinds of ethnomedicinal plants. Gujarat has a variety of vegetation in ethnobotany. This paper rise concern on loses of Traditional knowledge and plants varieties are destroyed by the knowledge loss and development of tribal human life.